Optimization of making process of api-api (Avicennia marina) mangrove leaves stew with response surface methodology analysis - Shofwatun Nida; Eko Nurcahya Dewi; Putut Har Riyadi (Universitas PGRI Semarang, 2022)
The leaves of the A. marina have the potential to be developed into functional foods such as tea. It contains alkaloids, saponins, tannins, phenolics, flavonoids, triterpenoids and glycosides, with antioxidants, antimicrobials, antifungals and antibiotics potential. This study want to examine the effect of oven duration and stewing duration on the stewing quality of A. marina leaves and to determine the optimum oven duration and stewing duration using analysis of Response Surface Methodology (RSM). The lower limit of the oven time used is 2 hours and the upper limit is 6 hours, while the lower limit for stewing is 5 minutes and the upper limit is 15 minutes. Analysis of the data carried out is a test for tannin levels, antioxidant activity test and hedonic test. Data of tannins and antioxidant activity processed using Software Design Expert 11. The progam suggests formulate with oven duration is 4 hours and stewing duration is10 inutes. The result of the tannin test are prdictd to produce 2.8676% and antioxidant activity 1.282 ppm. The desirability value is 0.961. that means the resulting formula is matchs.